Odpowiedzi

2009-11-30T15:00:26+01:00
A)

-3x + y = -5 / × (2)
5x - 2 y = 7

-6x + 2y = -10
5x - 2y = 7
+ ----------------------

-x = -3 / × (-1)
5x - 2y = 7

x = 3
5 × 3 - 2y = 7

x = 3
y = 4

b)

x - 3y = 5
3x + y = -5 /× 3

x - 3y = 5
9x + 3y = -15
+--------------------

10x = - 10 / ÷10
x - 3y = 5

x = -1
y = -2
2009-11-30T15:00:56+01:00
A)
5=3x-y
5x-2y=7

3x-y=5 |*5
5x-2y=7 |*(-3)

15x-5y=25
-15x+6y=-21

6y-5y=(-21)+25
y= 4

5=3x-y y=4
5=3x-4
3x=-4-5
3x=9 |/3
x=3

b)
x-3y=5
y+3x=-5 |*3

x-3y=5
3y+9x=-15

9x+x=-15+5
10x=-10 |/10
x=1

x-3y=5 x=1
1-3y=5
-3y=5-1
-3y=4 |/-3
y= -1 ⅓